PENGARUH INFLASI DAN PERGERAKAN NILAI TUKAR RUPIAH TERHADAP NERACA PERDAGANGAN INDONESIA - Fakhruddin Fakhruddin; Surya Rahmawati (Syiah Kuala University, 2021)
Abstract The purpose of this study is to determine the effect of inflation and exchange rate movement against Indonesia balance of trade conditions using time series data from January 2010 to December 2019 that are quantitative or in the form of numerical data.This research includes inflation data, rupiah exchange rate and trade balance sourced from Bank Indonesia (BI) and Badan Pusat Statistik (BPS) using vector error correction model (VECM) to see the long-term and short-term relationship in the trade balance. The results of this study concluded that there is a long-term and short-term relationship in the model through the cointegration test, in the long run inflation has a negative and significant effect on the trade balance, while the exchange rate has a positive and significant effect on the trade balance.